2001
DOI: 10.1002/pola.1307
|View full text |Cite
|
Sign up to set email alerts
|

Self‐initiating performance of maleic anhydride on surface photografting polymerization

Abstract: Maleic anhydride (MAH) was photografted onto low-density polyethylene (LDPE) films with a grafting efficiency of about 70% in the absence of a photoinitiator. The self-initiating performance was attributed to a mechanism of abstracting hydrogen atoms from LDPE chains by excited MAH dimers. The supporting experimental results were as follows: (1) the far-UV radiation (200 -300 nm) was indispensable for the graft polymerization and 2) the crosslinking reaction of LDPE inevitably accompanied the grafting of MAH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 11 publications
5
43
0
Order By: Relevance
“…Initiation Performance of MAH MAH, as a monomer, can also act as a photoinitiator under UV irradiation, which has been discovered and reported in our earlier article, 4 and it was further confirmed in this photografting system. First of all, the effect of BP concentration on the photografting was investigated and the results were shown in Figure 4.…”
Section: Activation Energy Of the Surface Photografting Polymerizationmentioning
confidence: 62%
See 1 more Smart Citation
“…Initiation Performance of MAH MAH, as a monomer, can also act as a photoinitiator under UV irradiation, which has been discovered and reported in our earlier article, 4 and it was further confirmed in this photografting system. First of all, the effect of BP concentration on the photografting was investigated and the results were shown in Figure 4.…”
Section: Activation Energy Of the Surface Photografting Polymerizationmentioning
confidence: 62%
“…This may offer a possibility for application to carry out the photografting polymerization without photoinitiator. Associating with our previous results 4 that MAH itself could readily undergo photografting in the absence of any photoinitiator and acrylic acid (AA) could perform photografting in the presence of MAH (without adding photoinitiator), the initiation performance of MAH in this photografting system can be naturally deduced.…”
Section: Activation Energy Of the Surface Photografting Polymerizationmentioning
confidence: 90%
“…19 The results showed that only when the irradiation time was prolonged to 3 min did the grafting efficiency reach 60%. This is because MAH is difficult to homopolymerize under usual conditions due to the great steric hindrance, as commonly considered, which leads to the difficulty of the grafting chain propagation.…”
mentioning
confidence: 76%
“…The photografting polymerization was carried out in the apparatus the same as that in the previous pa- pers, 19,23 which was built in our laboratory. The assembly for photografting polymerization is shown schematically in Figure 1, which is named "Film Interface Photopolymerization (FIP)" technique 9 used in our photografting operation.…”
Section: Photografting Polymerization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation